Orientations of professional discretion in the welfare service state - Tony Evans (Social Work and Society)
The idea of discretion has re-emerged as a positive attribute of professional practice in policy in the welfare service state. Flexibility and a consumer orientation have given rise to a new discourse of professionalism as a service orientation, which tends to be applied broadly in welfare services. The more traditional idea of discretion as space within which to exercise professional expertise has also received a boost, but it's expertise that should be oriented to specific purposes. In this presentation, I will draw on the developments in adult social care in England and consider four of these orientations that are central to the contemporary framing of professional discretion in working with service users in the service state: entrepreneurship; acting as a choice architect; safeguarding; and creative practice.